ANALISIS KEAMANAN WEBSITE PRODI SISTEM INFORMASI UINSU MENGGUNAKAN METODE APPLICATION SCANNING - Pria Mitra Purba; Azrah Cipta Amandha; Riyan Hidayah Purnama; Ali Ikhwan (Jurnal Informatika Teknologi dan Sains, 2022)
The current technological developments on security in every agency or agency website will certainly provide the best security, especially in terms of interfaces and data security. The website is an information page that is available through the internet so that it can be accessed throughout the world as long as it is connected to the internet network. The website itself is a component or collection of components consisting of text, images, sound, and animation so that it is interesting to visit. The Information Systems Study Program website is one of the websites that is able to provide academic information and the needs of UINSU Information Systems Study Program students. Therefore, of course, this website has its own security for processing existing data and information. Web security refers to protocol protection measures adopted by web managers to protect and secure data on websites and servers so that they are not exposed to cybercriminals or to prevent exploitation of the website in any way.